The Influence of Self-Efficacy and Motivation on Entrepreneurial Intentions Among Millennial Business Students - Melva Hermayanty Saragih; Shelvy Kurniawan (Universitas Nusantara PGRI Kediri, 2022)
Millennials are considered the most potential entrepreneurs because they are creative, innovative and self-educated. Millennials also have confidence and self-efficacy which greatly influences a person’s entrepreneurial intention. Moreover, based on some researches, motivation has an influence on a person’s entrepreneurial intention. The purpose of this study was to examine the effect of Self Efficacy and Motivation on Entrepreneurial Intention. The research was conducted using multiple linear regression. The number of respondents was 187 students in the last year of a business school in Indonesia. The results showed that Self Efficacy and Motivation both partially and simultaneously had a significant effect on Entrepreneurial Intention.